Planning and managing public relations campaigns : a stategic approach - Gregory, Anne (London : Kogan Page, 2021)
"Taking a public relations campaign from planning through to implementation can seem overwhelming. Planning and Managing Public Relations Campaigns provides a blueprint for success, and is widely regarded as one of the best 'how-to' guides for students and practitioners. Digestible and easy to read, this fifth edition presents a 12-point plan for ensuring success of campaigns of all sizes, covering vital areas including the role of public relations in organizations, the importance of context, research and analysis, setting objectives, strategy and tactics, timescales and resources, evaluation and review
1. Planning and managing in a changing world -- 2. The role of public relations in organizations -- 3. Planning and context - - 4. Starting and planning process -- 5. Research and analysis -- 6. Communication theory and setting aims and objectives -- 7. Knowing the stakeholders and content -- 8. Strategy and tactics -- 9. Timescales and resources -- 10. Knowing what has been achieved: evaluation and review
Includes bibliographical references and index
Keywords: Management; Public relations; Public relations -- Great Britain